Analisis Kebijakan Pemanfaatan Dan Pengelolaan Kawasan Waduk Cirata-Jawa Barat - Maria Maghdalena Diana Widiastuti (Universitas Lambung Mangkurat, 2019)
Cirata reservoir requires holistic management because the body of the reservoir crosses three administrative regions. Policies become important tools to address across boundary problems and externalities. The purpose of this study is to analyze the policy used in Cirata management and utilization. The methods are content policy analysis and gap analysis. The results of content analysis stated that the management and utilization of the reservoir have been arranged in sustainability manner. There were quotas of floating net and activity for preservation dam. Gap analysis states that there has been a high gap between the regulations and the implementation. Suggestion for the policy maker is to enforce the regulations and capacity building the actor who concerned for implementation regulation. Build institutional arrangements as a social movement to oversee the implementation of the policy.